RESAC: a redundancy strategy involving approximate computing for error-tolerant applications - Balasubramanian, Padmanabhan (2024)
Given the continuing miniaturization of underlying transistors, electronic functional units (circuits/systems) become increasingly susceptible to high-energy radiation, encountered in applications like space. Hence, redundancy is employed as a radiation hardening by design strategy to cope with faults of functional units used in such applications and to maintain their correct operation. Triple modular redundancy (TMR), which is a subset of N-modular redundancy (NMR), that can mask any single fault or a faulty functional unit has been widely used. However, compared to a simplex implementation a TMR implementation requires two additional functional units and a majority voting logic therefore a TMR implementation's area and power overheads are greater by over 200 %. This is burdensome for resource-constrained applications like space where low power and energy efficiency are important considerations. This paper presents a new redundancy strategy involving approximate computing called RESAC for error-tolerant applications such as digital image/video/audio processing, which is used in space systems. We evaluated the feasibility of RESAC for an image processing case study and the results confirm the usefulness. For implementation using a 28-nm CMOS technology, RESAC achieves reductions in area, delay, and power by 22.3 %, 15.3 %, and 24.9 % compared to TMR. Nonetheless, RESAC can address any NMR.